Mediating effect of institutions and moderating effect of culture on the relationship between IFRS adoption strategies and accounting quality - Alhammad, Abdullah Hammad (2020)
In recent years, the International Accounting Standards Board (IASB) has highlighted the importance of full adoption more than just convergence of accounting standards. While full adoption of IFRS eliminates accounting differences by allowing only the IFRS standards’ applications, convergence concentrates on certain major differences within the standards and differences in the enforcement levels. These differences, despite small ones, lead to significant impact on reported performance that hinders the objective of having globalized uniform standards. Examining the variations in IFRS adoption as reported by the IASB in its jurisdiction profiles has proven to be a paramount important since jurisdictions are described by the IASB to have employed different IFRS implementations which falls within the so-called enforcement strategy and modification strategy. Given the lack of research in this area, the present research attempts to address the gap by examining the relationship between IFRS enforcement and modification strategies and accounting quality across different jurisdictions around the world. Besides, the diversities in institutional settings such as the quality of institutional and cultural dimension, lead the study to further investigate the mediating effect of institutional quality on the relationship as well as the conditional effect of culture on the relationship between the different IFRS adoption strategies and accounting quality. Using the dynamic system of Generalised Method of Moments (GMM) estimation technique as the primary method of analysis, the study converts firm-level data on accounting quality which is based on 8836 listed firms in 35 developed and developing countries that adopted IFRS, into country-level data to reduce heterogeneity. The sample covers a period of 2013 to 2017, representing the stable years following the world global financial crisis and reflecting the years in which IFRS jurisdiction profiles are available. The findings suggest that IFRS enforcement and modification strategies are statistically significant in reducing discretionary accruals. Similarly, the adoption of IFRS with enforcement and modification has been found to be positively associated with timely loss recognition and value relevance. The results also show that both strategies have given significant positive impact on accounting quality by reducing the discretionary accruals at a higher magnitude, more than the increasing effect of timely loss recognition and value relevance. It is worth noting that the efforts made for IFRS enforcement strategy affect discretionary accruals and timely loss recognition more than the IFRS modification strategy. In terms of the indirect effects, the study reveals that institutional variables, especially the voice and accountability, government effectiveness, regulatory quality and control of corruption mediate the relationship between IFRS adoption strategies and the quality of accounting across countries, corroborating previous expectations. Furthermore, the effects of IFRS enforcement and modification on accounting quality vary with power distance, uncertainty avoidance, institutional collectivism, and future orientation. These indicate complementarities in which the effect of IFRS adoption strategies on the quality of accounting information depends positively on cultural variables. The current research involves numerous implications for policymakers, investors, and managers. It provides insightful information to understand the variations in IFRS enforcement and modification and their effects on accounting and the rule of the institutional environment and cultural dimensions within this relationship.